Geochemistry of Natural Gas Seepages in Boto Area, Bancak, Semarang, Central Java - Amijaya, Hendra; Pameco, Pracoyo Adi (Geological Agency, 2017)
DOI: 10.17014/ijog.4.2.61-70Three seepage gas samples collected from Boto Area, Bancak, Semarang, Central Java, were studied to determine their chemical characteristics using GC and GC-IRMS methods. They are composed 53 - 85% of methane predominantly. However, gas seep Site 3 sample has the highest N2 compound and the lesser extent to the samples Site 2 and Site 1 respectively. The two hydrocarbon gas seeps (Site 1, 2, and Site 3 samples) that are characterized by δ13C methane of -35.61‰ and -27.97‰, and values of δD methane of -112‰ and -109‰ respectively, are each isotopically distinct from all others suggesting, at least, they are derived from different maturity level. The Site 3 gas sample is suggested to be more mature than the others.